Predicative Structure of Multi-Clause Sentences Containing One-Member or Multi-Member Coordination Clauses in Old English (Based on Anglo-Saxon Chronicle) - Стыро, В. (Kalbotyra, 1975)
Predicative structure of multi-clause sentences consisting of one-member or multi-member coordination clauses is described. Coordination patterns and quantitative distribution of variant patterns are defined.